Evaluating Ecological Suitability and Carrying Capacity for Budo’s Mangrove Ecosystem: Unveiling Ecotourism Potential and Limits (International Journal of Scientific Research and Management (IJSRM), 2024)
Budo Village in North Sulawesi stands out as one of the top 50 recipients of the prestigious 2022 Indonesian Tourism Village Award. Notably, Budo is a popular tourist destination with a thriving mangrove area on Minahasa’s northern peninsula. The Budo mangrove area has been designated as a tourist attraction since 1994 and garnered increased recognition in 2017, thanks to active promotional efforts aimed at coastal tourist destinations. Surprisingly, despite its transformation into a tourist destination, research has yet to be undertaken to assess the ecological suitability of mangroves in this context or determine the carrying capacity of the mangrove area. This study seeks to delve into the ecological suitability of Budo’s mangrove ecological resources and investigate the carrying capacity of the area as a tourist destination. The results of this analysis categorize the Budo mangrove tourist destination as ’unsuitable,’ as indicated by an IKW score of 1.5. Consequently, a comprehensive restoration approach is required to render this mangrove area suitable and viable for tourism. Mangrove restoration initiatives, coupled with more stringent adherence to ecotourism principles in the Budo mangrove area, along with considerations for its carrying capacity, could serve as vital steps towards achieving this objective.